Modular Chiral Bithiophene‐2NO Ligands: Synthesis and Application in Asymmetric Palladium(II)‐Catalysed Friedel‐Crafts Alkylation - Zhu, Xian‐Qiao; Li, Wu‐Wu; Liu, Lin‐Lu; Xu, Ke‐Lan; Peng, Li‐Jun; Zhang, Min; Liu, Xiong‐Li; Zhang, Wen‐Jing (Advanced synthesis & catalysis, 2025)
The development of privileged thiophene‐type ligand remains highly desirable, owing to the high coordination ability of sulfur atom to most of the soft metals. Herein, a new class of C2‐symmetric rigid chiral tertiary amine‐derived dioxide ligands with a coordinating bithiophene bridge was developed in a convenient synthetic route with 25–62% overall yields. The bithiophene‐2NO‐palladium(II) catalyst system was generated in situ and found to be highly capable catalyst in the asymmetric Friedel‐Crafts alkylation of indoles. Excellent yields (up to 92%) and high enantioselectivities (up to >99% ee) are obtained for a wide range of substrates under mild conditions. Control experiments and DFT calculations revealed the origins of the enantioselectivity. This represented the first example of chiral thiophene ligands coordinating with soft metal Pd(II) in the asymmetric Friedel‐Crafts alkylation. Experiments revealed that the counteranion is involved in the stereoselectivity‐determining step in this soft palladium(II) catalysis, and the additional NO and thiophene in ligands can act as the second chelation site and thus reduce the amount of free metal ions for suppressing background reaction in the catalytic system.